Planejamento ambiental na cidade de São Carlos (SP) com ênfase nas áreas públicas e áreas verdes diagnóstico e propostas - Oliveira, Carlos Henke de (Universidade Federal de São Carlos, 1996)
This study has aimed to environmental planning on São Carlos City through the purpose of a classification system for public areas and public green areas, based on its structural, functional, utilitarian and legal attributes of public areas, to allow the social and environmental diagnosis based on population density, percentage of green areas and green area/population ratio to whole urban nucleus. The GIS (Geographical Information System) IDRISI provided a necessary support to development and application of operational models. The diagnosis of arborization allows determine 8 strategies that will operate over public and particular areas, aiming enhance the quality of environment and life. The proposition of implantation of new green areas was evaluated through prognosis. The results have shown 2.07 percentage of green areas. The green area/population ratio was 2.59 m2/person. The proposal of new areas for arborization would result at 6.98 m2/person, representing a real ameliorate from the present situation, however the prognosticated value was considerate low when comparing to other Brazilian cities. It was conclude that the Classification Model for Public Areas is adequate for the defined purposes and there is a need to review the specific legislation, therefore, planning and organizing the Local Government which would act effectively to accomplish the environmental policy.
Environmental planning on São Carlos City (São Paulo State: Brazil) with emphasis on the public and green areas: diagnosis and purposes
Keywords: Planejamento urbano; Ecologia urbana; Áreas verdes; Renovação urbana; CIENCIAS BIOLOGICAS::ECOLOGIA